A new quantitative evaluation method for drilling risk based on uncertainty analysis - Zhichuan Guan; Ya-Nan Sheng; Ming Luo; Yuqiang Xu; Bo Zhang; Qing Wang (Kuwait Journal of Science)
With drilling operations extending to offshore or deep and complex formations, drilling risk is becoming more and more serious. Traditional methods cannot assure the safety of high-risk drilling operations. Therefore, establishing a quantitative evaluation method for drilling risk is becoming increasingly more urgent. In this paper, the credibility of formation pressure and equivalent circulation density (ECD) of drilling fluid were first analyzed based on the Monte Carlo simulation method. Thereafter, the probability distributions of formation pressure and ECD were obtained. Then, based on the generalized stress and strength interference theory, the quantitative method for evaluating drilling risk was established. In this method, the risk factor was defined as the generalized stress (ECD). The safety factor was defined as the generalized intensity (formation pressure). The safety barrier function was defined as the function of drilling risk. In two case studies, this method was used to predict drilling risk probabilities, and the prediction results were in favorable agreement with the actual drilling risk.